THE APPROPRIACY OF ASSESSMENT IN THE JUNIOR HIGH SCHOOL ENGLISH TEXT BOOKBASED ON THE 2013 CURRICULUM - Siti Tariwyah (Vision: Journal for Language and Foreign Language Learning, 2014)
Assessment is one of important means to identify the success of learning process, since it gives information about students’ competence, which is in line with learning aims or targetted competence. Information from assessment may be used as the consideration to set the policy of teaching learning process.The 2013 curriculum emphasizes more on authentic assessment, encompassing knowledge, skill, and attitude. Through this assessment, good attitude building as one of the priorities of the curriculum may be realized. cognitive and psychomotoric domains variedly in the student book. But affective domain, as the ﬁrst priority of the curriculum has not been provided by instrument in the student book and clear instruction on how to proceed it in the teacher book.